تغير معاملات دالة الهدف لمسالة النقل وتأثيرها على الحل الأمثل للمسألة (Journal of Humanitarian and Applied Sciences, 2018)
In this work, we care about the impact study on the transport problems (which is a linear programming problem) in terms of the type of solution and the value of the objective function when you change a value cost factor (cij ) to increase or decrease and for this purpose, we study 4 different problems and for this, we used two methods the first one called (The method of least cost) and the second one is called (The method of vogal)and we used these two methods to compare between the solutions and which solution gives us the least possible value for the objective function.The values of the factor of the objective function that we've studied can exist in one period or more than one period, and in each case, there exists one kind of solution or more than one solution and for each solution, there exists a value of the objective function. On this basis, we found several types of (a pattern solution) and these patterns repeat at the results of the problems To change the value of the factor (cij ) to obtain a particular solution and to ask If this solution is the same as the initial solutions which we obtained by the two methods or is different and we must determine if the current value is equal to the initial value or less than or greater than.